CLINICAL AND SUBCLINICAL CHARACTERISTICS AND FACTORS ASSOCIATED WITH LOW BONE MINERAL DENSITY IN TRANSFUSION-DEPENDENT THALASSEMIA PATIENTS AT VIET TIEP FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and subclinical characteristics and to identify factors associated with low bone mineral density (BMD) in transfusion-dependent thalassemia (TDT) patients at the department of Clinical Hematology, Viet Tiep Friendship hospital.Methods: A cross-sectional descriptive study was conducted. Clinical data, laboratory tests, and BMD measured by DEXA were collected for all patients. Low BMD was defined as a Z-score < -2.0, and its association with patient characteristics was analyzed.Results: The prevalence of low BMD was 45.1%, with a median Z-score of -2.2 (-4.5 – 1.1). Mean hemoglobin was 76.3 ± 9.7 g/L, with most patients having moderate to severe anemia (92.2%). Median ferritin was 2322.9 (438.5–7545.0) ng/mL, with 82.3% of patients having ferritin > 1000 ng/mL. Factors significantly associated with low BMD included disease severity (p < 0.05), poor adherence to iron chelation therapy (92.9% vs. 69.6%; p < 0.05), lower hemoglobin (72.3 ± 9.9 vs. 80.9 ± 7.6 g/L), higher serum iron (34.5 vs. 26.3 µmol/L), and higher ferritin (2775.0 vs. 1394.0 ng/mL).Conclusion: Low BMD is a common complication in TDT patients, associated with disease severity, chronic anemia, iron overload, and poor adherence to iron chelation therapy.
Keywords: Transfusion-dependent thalassemia, bone mineral density, ferritin, hemoglobin.